2021
DOI: 10.1007/s41669-020-00249-0
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing in Clinical Practice: Is It a Cost-Saving Alternative to a Single-Gene Testing Approach?

Abstract: Objectives This study aimed to compare the costs of a next-generation sequencing-based (NGS-based) panel testing strategy to those of a single-gene testing-based (SGT-based) strategy, considering different scenarios of clinical practice evolution. Methods Three Italian hospitals were analysed, and four different testing pathways (paths 1, 2, 3, and 4) were identified: two for advanced non-small-cell lung cancer (aNSCLC) patients and two for unresectable metastatic colon-rectal cancer (mCRC) patients. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Moreover, sequencing‐based approaches are a promising approach for the diagnosis of infectious disease because a comprehensive spectrum of potential causes—viral, bacterial, fungal, and parasitic—can be identified by a single assay, even when new, emerging pathogens are concerned such as SARS‐CoV‐2. [ 30 , 31 , 32 ] Being relatively cheap and straightforward, mNGS (mainly using Illumina platforms) is the major sequencing‐based pathogen detection, and mtNGS developed in our study (added reverse transcription) only incurs very limited extra cost. In comparison, TGS platforms such as ONT and Pacbio are still in their early developing stage and relatively costly, especially considering the reduced sequencing outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sequencing‐based approaches are a promising approach for the diagnosis of infectious disease because a comprehensive spectrum of potential causes—viral, bacterial, fungal, and parasitic—can be identified by a single assay, even when new, emerging pathogens are concerned such as SARS‐CoV‐2. [ 30 , 31 , 32 ] Being relatively cheap and straightforward, mNGS (mainly using Illumina platforms) is the major sequencing‐based pathogen detection, and mtNGS developed in our study (added reverse transcription) only incurs very limited extra cost. In comparison, TGS platforms such as ONT and Pacbio are still in their early developing stage and relatively costly, especially considering the reduced sequencing outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the importance of NGS-driven, high-tech screening and diagnostics have been given new prominence by the exigencies of the COVID-19 pandemic; the continually rising burden of cancer in Europe [57] has also lent new significance to technologies that can deliver more selective and effective treatments, with benefits for health budgets as well as for patients. For example, in advanced non-small cell lung cancer, NGS has been shown to have a modest budget impact for payers, with the potential to better enable selection for targeted therapy and clinical trial enrollment [58][59][60][61].…”
Section: Relevant Recent and Upcoming Ngs-related Initiativesmentioning
confidence: 99%
“…In addition, recent studies have shown that by implementing NGS-based testing, clinics can reduce the cost required for evaluating biomarkers specifically for targeted treatments or agnostic therapy implementation. NGS-based testing can reduce total testing cost by EUR 30–1249 depending on how comprehensive the analysis is, when compared to RT-PCR technology [ 80 ].…”
Section: Ngs In Lung Cancer Diagnosismentioning
confidence: 99%